Analisis Yuridis Pemberian Remisi Bagi Anak Yang Dipidana Penjara Di Bawah Satu Tahun Di Lembaga Pembinaan Khusus Anak Menurut Undang-Undang Republik Indonesia Nomor 12 Tahun 1995 Tentang Pemasyarakatan - Akmal, Rifki (Lex Librum : Jurnal Ilmu Hukum, 2022)
Everyone has the right to a remission or reduction in the term of sentence. However, in practice, a prisoner sentenced to less than one year of imprisonment will not receive a reduction during his term. With a criminal fall under one year, prisoners can return to their families and surrounding communities as well as participate in the development. This research uses empirical law research methods. Juridic analysis of the granting of remission to children sentenced to imprisonment under one year in a child special training institution according to the Law of the Republic of Indonesia No. 12 of 1995: Implementation of the remission must take into account the effectiveness of criminal prison in the Lapas Rutan in Indonesia, which can be reviewed from the fundamental aspects of the purpose of the funding, namely the protection of the public and the aspects the perpetrator. First, the first and second phases of advanced construction begin after the prisoners enter Lapas